Line of Sight Implementation for Game Platformer - Andika Eko Kristanto; Lailatul Husniah; Ali Sofyan Kholimi (Universitas Muhammadiyah Malang, 2019)
Traditional weapon is one of cultural heritage from our ancestors in Indonesia. While it can be noted that the popularity of less traditional weapons in the know by many people because it is losing popularity with weapons from other countries. But now there are some people who make use of media technology to preserve the traditional cultures ranging from custom homes, traditional clothing and also a traditional weapon from every province in Indonesia. Be aware that in Indonesia traditional weapon there are diverse, but some provinces have the same traditional weapons it can because the province having the same family or experience the separation area. So on the development level, authors will make the concept of continuous Boss for some provinces that have same traditional weapons. In addition to developing a level of the game, the author also applied line of sight method on the boss enemy.